Soil organic pollution and ecological risk assessment in brownfield soil from Northwest China: an integrated analysis of man-land interrelations - Wang, Luyao; Xie, Xiao; Liu, Siqi; Wang, Jing; Peng, Biao; Sun, Yingying (Frontiers in Environmental Science, 2023)
In general, chemical plants are accompanied by a variety of secondary production in the production process, which may have different degrees of impact on the environment. At the same time, in order to ensure the environmental safety of new urban construction land, it is necessary to conduct pollution investigation and further environmental risk assessment on potentially polluting abandoned chemical plants. This paper takes a chemical plant producing food grade fumaric acid in Northwest China as an example to investigate the pollution of organic matter in the soil in accordance with relevant standards, then analyzes the vertical pollution degree of key pollution areas. The calculation results of single factor pollution index and Nemerow pollution index show that there are 17 kinds of organic pollutants that exceed the screening value in land of Class I. Among them, benzene, 1,2,3-trichloropropane and 1,1,2,2-tetrachloroethane are most serious, and the highest exceeded the standard by 11311 times.Moreover, the distillation zone and the reactor zone have reached the level of V pollution, and the maximum pollution depth can reach more than 6 m. The results of HERA software analysis showed that there were 18 and 10 kinds of organic pollutants with carcinogenic risk values exceeding 10-6 in the reactor and distillation area, respectively, and 25 and 11 kinds of organic pollutants with hazard quotients exceeding 1, respectively. According to relevant regulations, the contaminated areas with unacceptable regional risks must be properly repaired.